Perbandingan Ekstraksi Oleoresin Biji Pala (Myrictica Fragrans Houtt) Asal Maluku Utara Menggunakan Metode Maserasi dan Gabungan Distilasi – Maserasi - Muhammad Assagaf; Pudji Hastuti; Chusnul Hidayat; Supriyadi Supriyadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2012)
The purpose of this study was to compare the composition of oleoresin nutmeg (Myristica fragrans Houtt) madedirectly by maceration and combined distillation – maceration. Nutmeg oleoresin yield amounted to 15.17±0.07 (% db)obtained by direct maceration and oleoresin extraction method combined distillation and maceration obtained yield of20.07±0.23 (% db). While the essential oil yield itself from the water-steam distillation of the results obtained at 6.61(% db). Ethanol extract of oleoresin analysis using GCMS method identiÞ ed a total of 39 kinds of compounds withthe composition of major components is methyleugenol (33.40 %), myristicine (10.90 %), cis-methyl isoeugenol (9.09%), elemicin (8.33 %), and isocoumarin (5.61 %). For nutmeg essential oil contained 31 components of the compound,where the components are located in large numbers was sabinene (34.97 %), !-phellandrene (19.9 %), methyleugenol(7.55 %), myristicine (5.29 %) and elimicine (3.21 %). As for the essential oil is mixed with the oleoresin from the pulpremaining distillation contained 58 components that make up the compound of the oleoresin with a mixture of maincomponents, namely: sabinene (12.38 %) myristicine (10.88 %), elemicin (8.93 %), isocoumarin (6.26 %), myristicacid (5.96 %), and